Biosynthesis and Regulation of Phenylpropanoids in Plants - Deng, Yuxing; Lu, Shanfa (Critical reviews in plant sciences, 2017)
Phenylpropanoids are a large class of plant secondary metabolites derived from aromatic amino acids phenylalanine in most plants or tyrosine in partial monocots. It mainly includes flavonoids, monolignols, phenolic acids, stilbenes, and coumarins. Phenylpropanoids are widely distributed in the plant kingdom and play vital roles in plant development by acting as essential components of cell walls, protectants against high light and UV radiation, phytoalexins against herbivores and pathogens, floral pigments to mediate plant-pollinator interactions. In addition, phenylpropanoids possess diverse biological activities that are beneficial to human health. In the past decades, the structure and function of phenylpropanoids and the biosynthetic pathways of flavonoids, monolignols and phenolic acids have been extensively studied. Recent results showed that miR828, ta-siRNAs and R2R3-MYBs play critical regulatory roles in phenylpropanoid biosynthesis through two modes: either the miR828-MYB-phenylpropanoid biosynthesis cascade in which MYB transcripts are directly cleaved by miR828, or the miR828-ta-siRNA-MYB-phenylpropanoid biosynthesis cascade under the mediation of TAS4- or MYB-derived ta-siRNAs. In this review, we overview the structure, function and biosynthetic pathway of phenylpropanoids and summarize the complex regulatory mechanism of phenylpropanoid biosynthesis with a focus on the two cascades involving miR828, ta-siRNAs and MYBs.